2020
DOI: 10.1007/s12250-020-00329-9
|View full text |Cite
|
Sign up to set email alerts
|

Viral and Antibody Kinetics of COVID-19 Patients with Different Disease Severities in Acute and Convalescent Phases: A 6-Month Follow-Up Study

Abstract: Coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has spread rapidly around the world, posing a major threat to human health and the economy. Currently, long-term data on viral shedding and the serum antibody responses in COVID-19 patients are still limited. Herein, we report the clinical features, viral RNA loads, and serum antibody levels in a cohort of 112 COVID-19 patients admitted to the Honghu People’s Hospital, Hubei Province, China. Overall, 5.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
47
3
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(70 citation statements)
references
References 32 publications
17
47
3
2
Order By: Relevance
“…Our studies demonstrated that NAb, IgA, and total levels of IgG and IgM were not correlated with viral load in COVID-19 patients, while a weakly inverse correlation between IgG subclasses and viral load was observed. Our findings are consistent with two prior studies, which also reported no correlation between persistent SARS-CoV-2 RNA and NAb titers ( 24 , 40 ). Slim Fourati et al reported a lower early antibody responses were related to higher viral load in nasopharyngeal swabs in the severely ill COVID-19 patients ( 41 ), though the study may be limited by its smaller sample size.…”
Section: Discussionsupporting
confidence: 93%
“…Our studies demonstrated that NAb, IgA, and total levels of IgG and IgM were not correlated with viral load in COVID-19 patients, while a weakly inverse correlation between IgG subclasses and viral load was observed. Our findings are consistent with two prior studies, which also reported no correlation between persistent SARS-CoV-2 RNA and NAb titers ( 24 , 40 ). Slim Fourati et al reported a lower early antibody responses were related to higher viral load in nasopharyngeal swabs in the severely ill COVID-19 patients ( 41 ), though the study may be limited by its smaller sample size.…”
Section: Discussionsupporting
confidence: 93%
“…The in silico studies indicated that HIV-1 protease inhibitors Lopinavir and Ritonavir (Nutho et al 2020 ) is a novel M pro inhibitors. However, in vitro and in vivo studies showed that these inhibitors could not reach the effective pharmacokinetic concentration for inhibiting M pro (Zhang et al 2020b ).…”
Section: Similarity Of Sars-cov-2 With Other Coronavirusesmentioning
confidence: 99%
“…Whether for enzyme immunoassay-detected antibody (or similar) or neutralizing antibody, the total specific antibody level peaks after 3-10 weeks [30,[51][52][53][54][55][56][57][58][59][60]. As anticipated, IgM reactivity diminishes over the first few months while IgG reactivity continues to be detected for a much longer interval [54,56,57,59,[61][62][63][64][65][66][67]. The finding of rapid IgG response relative to IgM suggests a possible priming from past exposure to endemic respiratory coronaviruses [34].…”
Section: Immunogens and Humoral Immunitymentioning
confidence: 80%
“…Different antibody responses decay variably and dependent on the nature of the antibody target and severity of disease [33,50,54,59,61,68,75,76,78,83,87,95,96,[100][101][102][103]. The latter includes measurable neutralizing antibody, and the decay in some patients after 1 month can be such that donations with desirable high titres elapse quickly in convalescence after infection [49,54,[103][104][105][106].…”
Section: Immunogens and Humoral Immunitymentioning
confidence: 99%